A Study on Mathematical Short-term Modelling of Environmental Pollutant Transport by Sea Currents: The Lagrangian Approach - Kordas, Olga; Gourjii, Alexandre; Nikiforovich, Eugene; Cherniy, Dmytro (Journal of Environmental Accounting and Management, 2026)
This paper deals with short-term modelling of pollutant transport on the sea surface after environmental accidents. Using the Lagrangian approach, a two-dimensional model of pollutant flow is developed to determine the average velocity field of the flow in the presence of tidal currents and sea surface wind stress for an arbitrarily shaped coastline. This approach assumes that the main transport mechanism is convection. Short-term scenarios are considered, where diffusion effects on pollutant transport can be neglected. The hydrodynamic problem is solved by the method of discrete singularities adapted to fluid advection problems. The problem of environmental pollutant transport by sea currents is reduced to integration of the advection equations to determine the spatio-temporal properties of the spreading pollution. The model was verified through comparison of the results against natural observations on the spread of an oil spill on the sea surface following a collision between the Chinese bulk carrier Fu Shan Hai and the Cyprian container ship Gdynia near the island of Bornholm in the Baltic Sea (May 31, 2003). Satisfactory agreement was found between results of a 7-day numerical simulation and observed data. The proposed model can therefore be used for real-time prediction of short-term pollutant transport on a sea surface with an arbitrarily shaped coastline, to support decision-making processes during maritime accidents, in particular oil spills.